SOSIALISASI PESTISIDA BOTANI UNTUK PENGENDALIAN HAMA DAN PENYAKIT TANAMAN JAHE DI NAGARI SUNGAI TALANG KECAMATAN GUGUAK KABUPATEN LIMAPULUH KOTA - Yulmira Yanti; Hasmiandy Hamid; Lora Triana; Irwin Mirzah Umami; Noveriza Hermeria; Megha Putri Tanjung (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2023)
The innovation farmer group Jorong Belubus, Nagari Sungai Talang is one of the villages in Guguak District, Limapuluh Kota Regency which has the potential to produce vegetable pesticides. This is supported by the many types of weeds such as Piper aduncum, babandotan and Surian plants that can be used as basic ingredients for making botanical pesticides. For the people of Nagari Sungai Talang, agricultural waste such as weeds are only considered as parasites for other crops. Communities and farmers in this area do not know how to process the waste of weeds and Surian leaves into quality products that can be used as biological agents for pest control. The purpose of this farmer group empowerment activity is to provide knowledge about weeds and forage plants that can be used as botanical pesticides and provide knowledge related to the process of making these botanical pesticides so that they can be used as pest control agents. The method used is structured training and direct practice of making botanical pesticides in the field. The results obtained from this empowerment activity are that farmer groups are able to make botanical pesticides independently by utilizing weeds and other forage plants in the surrounding environment as agents of pest and disease control in cultivated plants.